LA METODOLOGÍA STERNBERG PARA EL APRENDIZAJE DE QUÍMICA INORGÁNICA II, CON LOS ESTUDIANTES DE TERCER SEMESTRE DE LA CARRERA DE PEDAGOGÍA DE LA QUÍMICA Y BIOLOGÍA, PERIODO OCTUBRE 2018- ABRIL 2019 - Jiménez Díaz, Dayana Magdalena (2019)
For Sternberg "Intelligence is all mental activity that orients the conscious adaptation to the environment and the transformation of this one, with the purpose of predicting results being able to actively provoke adaptations from oneself to the environment or from the background to oneself". The problem settles at weak knowledge about Sternberg’s methodology into teaching-learning process of inorganic chemistry II, the objective is: to describe the applicability of Sternberg’s methodology at learning inorganic chemistry II, with third semester students pedagogy of chemistry and biology, design of investigation was, not Experimental, because the methodologies that the teacher uses, without intervening in the process of teaching learning they were only observed, In addition the types of investigation used were field, bibliographic and longitudinal. In order to collect the information, the following technique used was survey and as instrument the questionnaire which consists in 10 multiple choice questions. According to obtained results it is concluded that the research is of great relevance at academic and professional training of students, because it allows to bond practice with theory, as well the development of Pedagogical-experimental competences and strengthening teaching learning process. The applicability of Sternberg’s methodology within classroom is recommended because it contributes to development of professional competencies in the future pedagogues training and thus will be achieved to challenge knowledge and not blindly accept the Information.